2020
DOI: 10.3389/fcell.2020.566494
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Phosphorylase B Is Regulated by miR101-3p and Promotes Hepatocellular Carcinoma Tumorigenesis

Abstract: Glycogen metabolism plays a key role in tumorigenesis. High expression levels of glycogen phosphorylase B (PYGB) were reported in several cancers and might be served as a prognostic biomarker for cancer from precancerous lesions. Previous studies indicated the high expression of PYGB in hepatocellular carcinoma (HCC) tissues. However, the detailed roles of PYGB in HCC, as well as the regulatory mechanisms, are still unclear. In this study, we confirmed that PYGB was overexpressed in HCC tissues. PYGB overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…miR-101 is a downregulated miRNA in HCC tissues and its expression was negatively associated with a poor prognosis of HCC patients ( 29 ). By targeting several oncogenes, such as Enhancer of Zeste 2 Polycomb Repressive Complex 2 Subunit (EZH2), Dual-specificity phosphatase (DUSP), Myeloid cell leukemia-1 (Mcl-1), miR-101 exerts as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…miR-101 is a downregulated miRNA in HCC tissues and its expression was negatively associated with a poor prognosis of HCC patients ( 29 ). By targeting several oncogenes, such as Enhancer of Zeste 2 Polycomb Repressive Complex 2 Subunit (EZH2), Dual-specificity phosphatase (DUSP), Myeloid cell leukemia-1 (Mcl-1), miR-101 exerts as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-101-3p induced M1 to M2 macrophage-type conversion and enhanced cell migration of breast and ovarian ( Zhao et al, 2021 ). MiR-101-3p promoted hepatocellular carcinoma carcinogenesis by targeting glycogen phosphorylase B ( Cui et al, 2020 ). Li et al (2019) reported that miR-101-3p targeted TRIM44 to inhibit EMT and suppress glioblastoma cell proliferation metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The glycogen metabolism plays a key role in tumorigenesis. Not only PYGM, but also PYGB level is up-regulated in different kinds of cancer such as colorectal cancer [ 69 ], hepatocellular carcinoma [ 70 ], prostate cancer [ 71 ], non-small cell lung cancer (NSCLC) [ 72 ], and ovarian cancer [ 73 ]. However, one should keep in mind that carcinogenesis is a complex process in which many factors interact together [ 74 ].…”
Section: The Biological Importance Of Pygmmentioning
confidence: 99%